Coaching Teachers to Use a Simultaneous Prompting Procedure to Teach Core Content to Students With Autism. (August 2017) - Tekin-Iftar, Elif; Collins, Belva C.; Spooner, Fred; Olcay-Gul, Seray
The researchers in this study used a multiple baseline design across dyads to examine the effects of professional development with coaching to train general education teachers to use a simultaneous prompting procedure when teaching academic core content to students with autism and the effects of the procedure on the students' outcomes. Three teacher–student dyads participated in the study. Results showed that (a) teachers acquired the ability to use the simultaneous prompting procedure with 100% accuracy, maintained the acquired teaching behaviors over time, and generalized them in teaching new academic content to their students; and (b) students acquired the targeted academic content, maintained it over time, and generalized it across different persons and settings. In addition, the students acquired instructive feedback stimuli added to instruction and maintained these over time as well. Last, both the opinions of the teachers and students about the social validity of the study were positive. Future research is needed to support these findings.